Dissimilar Pile Raft Foundation Behavior under Eccentric Vertical Load in Elastic Medium - Ke Hu; Kaiyu Jiang; Xiaoying Gou; Wentao Wei; Lei Yan; Tingqiang Zhou; Zhengchao Guo; Guanwen Chen (Buildings, 2023)
Pile raft foundation (PRF) is a common foundation type for buildings and bridge piers which has been commonly subjected to eccentric vertical load in engineering applications. Dissimilar PRF is often adopted to reduce the excessive settlement and differential settlement of superstructures. The behavior of dissimilar PRF under eccentric vertical load is a significant issue and investigated with the boundary element method in this paper. In this method, the dissimilar pile–soil system is decomposed into extended soil elements and fictitious pile elements. The second kind of Fredholm integral governing equation of the axial force of fictitious piles is established based on the compatibility condition of axial strain between the extended soil and fictitious piles. An iterative procedure is adopted to analyze the average settlement w and rotation slope θ of raft stemming from the settlement compatibility condition of the top of each element and the equilibrium condition of the raft. Furthermore, the axial force and settlement of each element along its depth can be predicted. The corresponding results agree well with a reported case and the finite element method. The characteristics of 3 × 1 and 3 × 3 dissimilar PRFs under eccentric vertical load, including non-dimensional vertical stiffness N0/wEsd, differential settlement wd and the load sharing ratio of typical elements Ni/N0, are systematically investigated by considering different eccentricity e, length/diameter ratios of pile l/d and pile–soil stiffness ratio Ep/Es conditions. The N0/wEsd increases with l/d, while the load sharing ratios of the raft Nraft/N0 and wd decreases with l/d. The eccentricity e has a significant effect on wd and Ni/N0 and a neglect effect on N0/wEsd and Nraft/N0. The N0/wEsd, wd and Ni/N0 are significantly increased with Ep/Es. This research is expected to provide insights to the practitioners into the dissimilar PRF design under eccentric vertical load.